PELAKSANAAN STRATEGI BISNIS DAN PEMASARAN PT. BLUE BIRD, TBK - Iwan Kurniawan Subagja (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
The improvement in Indonesia's economy gradually is the result of the construction carried out during this causes additional income and consumer spending patterns. Changes in spending patterns and consumer spending was particularly noticeable for those who live in urban areas, especially large cities. The long experience of managing a transport business to support the company's efforts to develop new technologies and managing human resources, in order to stay ahead. From its headquarters in Jakarta, the company has developed rapidly penetrated other business while maintaining customer service as a guide. The long experience of managing a transport business to support the company's efforts to develop new technologies and managing human resources, in order to stay ahead. From its headquarters in Jakarta, the company has developed rapidly penetrated other business while maintaining customer service as a guide. Competition taxis in big cities, especially Jakarta, was now so tight, so the service is more preferred. Hence the need for a good strategy to win the competition and maintain market share. One was in the company of Blue Bird Group doing business and marketing strategies to win the competition and maintain market share taxi transportation in Indonesia. Research methodology in this case with the SWOT analysis, five Poter’s, matrix’s space and marketing analysis. Methods of data collection is done by conducting research directly related to the company in order to obtain the necessary data, that is by interview and observation. The result of research is adding fleet, increasing coverage at the new location, especially at the level of municipalities, improve service quality and level effesiensi operation, increase limousine division in several cities, improve prifitabilitas company. Advantage of the company at PT Blue Bird was in corporate governance, natural environmental management company, in the management of seasonal factors, the application of information technology, the implementation of safety standards and management.